Surgical Trends in Articular Cartilage Injuries of the Knee, Analysis of the Truven Health MarketScan Commercial Claims Database from 2005-2014 - Nicholas A. Bonazza, M.D; Dallas M. Smuin, M.D; Rajat Joshi, B.S; Djibril Ba, M.P.H; Guodong Liu, Ph.D; Douglas L. Leslie, Ph.D; Aman Dhawan, M.D (Elsevier, 2019)
Purpose: To evaluate trends in procedures for the treatment of chondral injuries of the knee using the MarketScan database in the hope that further work can be performed to refine the indications for chondral intervention Methods: The MarketScan Research Database was searched using Current Procedure Terminology, 4th edition, codes to identify patients who underwent chondral procedures of the knee from 2005-2014. Combined procedures, including meniscal transplant or osteotomy, were also identified. Patients were characterized by gender, age group and year of initial procedure. A χ2 test was used to evaluate differences in surgical trends between individual patient groups delineated by age and gender. The Cochran-Armitage trend test was used to identify significant differences in surgical trends yearly. Results: Of 148,373,254 unique patients, 520,934 patients underwent a total of 599,119 procedures. Arthroscopy with debridement/shaving of articular cartilage decreased in proportion from 75% of all procedures in 2005 to 51% of all procedures in 2014 (P < .0001). Open osteochondral allograft saw the greatest change during the study period; a higher number of females than males underwent condral procedures (P < .0001). Patients aged 45-54 underwent the most procedures (32.9% of all procedures). A total of 483 patients underwent chondral procedures in conjunction with meniscal transplant with variable incidence during the study period. A total of 1,418 patients underwent chondral procedures in conjunction with osteotomy; cumulative incidence decreased from 4.5 procedures per 1,000,000 patients/year in 2005 to 2.6 procedures per 1,000,000 patients/year in 2014 (P < .0001). Conclusions: Knee arthroscopy with debridement/shaving of articular cartilage remains the most common procedure performed. Although open allograft and autograft transplantation saw a sustained increase in incidence, the overall incidence of cartilage procedures, as well as those performed with osteotomies, declined. Level of Evidence: Level IV, cross-sectional study.